An Integrative Framework For Knowledge Management Capability, Information Security Compliance, And Internationalization - Wipawayangkool, Kamphol (Journal of Knowledge Management Practice, 2010)
This paper addresses two topics contemporary to both knowledge management and internationalization phenomena. First, in this information-sensitive era, internationalizing firms are typically required to comply with the host country’s information security regulations. Second, with the emergence of virtual teams, how virtual teams affect knowledge management capability and subsequently internationalization becomes relevant to many modern firms. Specifically, drawing from organizational information processing theory, this paper proposes an integrative framework by examining the influence of the fit between knowledge management capabilities particularly contributed by the effectiveness of knowledge creation processes in virtual teams and the extent of information security compliances on the extent of internationalization of the firms. Unlike much of prior academic literature focusing on American firms, this paper discusses how certain American security compliances possess challenges for foreign firms attempting to internationalize their businesses. Implications for researchers and managers are discussed.